PENGARUH PERILAKU KONSUMEN DAN MEREK PRODUK TERHADAP MINAT BELI PRODUK HERBA PENAWAR ALWAHIDA INDONESIA DI CIKARANG UTARA - Ririn Uke Saraswati (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the extent to which the variables of consumer behavior and product brand influence purchase intention, both partially and simultaneously. This associative study uses a quantitative approach with purposive sampling technique, which involves selecting respondents based on specific criteria who have previously used Alwahida Indonesia's Herbal Remedies. Data was collected from 100 respondents in the Cikarang Utara area using a questionnaire, employing the Purba formula. Data analysis was conducted using multiple linear regression analysis with the assistance of IBM SPSS 23.0, preceded by instrument testing and classical assumption testing. Consumer behavior partially influences purchase intention, with a calculated t-value of 8.954 > tabulated t-value of 1.984, and a significance level of 0.00 < 0.05. Product brand partially influences purchase intention, with a calculated t-value of 7.478 > tabulated t-value of 1.984, and a significance level of 0.00 < 0.05. Simultaneous testing yielded an F-value of 51.131 > tabulated F-value of 3.09, with a significance level of 0.00 < 0.05, indicating that the independent variables, consumer behavior, and product brand, collectively have a significant influence on the dependent variable, purchase intention.